2021
DOI: 10.1128/mbio.03102-20
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biological Functions of the NsdC Transcription Factor in Aspergillus fumigatus

Abstract: The fungal zinc finger transcription factor NsdC is named after, and is best known for, its essential role in sexual reproduction (never in sexual development). In previous studies with Aspergillus nidulans, it was also shown to have roles in promotion of vegetative growth and suppression of asexual conidiation. In this study, the function of the nsdC homologue in the opportunistic human pathogen A. fumigatus was investigated. NsdC was again found to be essential for sexual development, with deletion of the ns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 87 publications
1
15
0
Order By: Relevance
“…During this process, the initiation of asexual reproduction is repressed through the suppression of the developmental inductive transcription factor gene brlA , a conserved essential conidiation gene in fungi, and its upstream developmental activation pathway ( 27 ). Previous studies have verified that in the model filamentous fungus A. nidulans or A. fumigatus , dysfunction of NsdC, NsdD, MpkB, VosA, SfgA, VeA, or VelB results in the activation of conidiation after a period of vegetative growth under liquid culture conditions ( 26 28 , 30 , 34 ), suggesting that negative regulators exist for suppressing submerged conidiation to maintain constant vegetative growth with increasing mycelial pellets.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…During this process, the initiation of asexual reproduction is repressed through the suppression of the developmental inductive transcription factor gene brlA , a conserved essential conidiation gene in fungi, and its upstream developmental activation pathway ( 27 ). Previous studies have verified that in the model filamentous fungus A. nidulans or A. fumigatus , dysfunction of NsdC, NsdD, MpkB, VosA, SfgA, VeA, or VelB results in the activation of conidiation after a period of vegetative growth under liquid culture conditions ( 26 28 , 30 , 34 ), suggesting that negative regulators exist for suppressing submerged conidiation to maintain constant vegetative growth with increasing mycelial pellets.…”
Section: Discussionmentioning
confidence: 90%
“…However, based on these data alone, we could not exclude other possible mechanisms whereby submerged conidiation induced by the CBC mutants is due to derepression of other negative regulators of conidiation. In A. nidulans or A. fumigatus , it has been reported that the vosA , veA , velB , sfgA , nsdC , nsdD , and mpkB mutants also displayed asexual conidiation phenotypes similar to those of the CBC mutants in liquid medium ( 26 28 , 30 , 34 ). We then compared the expression differences of the abovementioned genes in the hapB mutant and its parental wild-type strain.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…One transcription factor is a homologue of the general stress response regulator AtfA [40]. Three transcription factors which, upon deletion, reduced the resistance towards sorbic acid are homologues of genes regulating siderophores and iron uptake, HapX, NsdC and AcuK [42][43][44]. AcuK is known to be essential for growth on gluconeogenic carbon sources, and its reduced resistance could possibly be caused by a metabolic imbalance and reduced catabolism of sorbic acid.…”
Section: Discussionmentioning
confidence: 99%